A Review of E-Government Services - Alan, Ngoh; Hasan, Maruf (Advances in Social Sciences Research Journal, 2015)
The recent developments of Information and Communication Technologies mainly the internet has made citizens accustomed to the convenience of online services such as e-banking and shopping online. Governments are aware of the benefits and needs of citizens thus leading to the development of e-government. The aim of this paper is to review the current state of e-government in Australia with the use of empirical studies. The review of e-government shows that the general use of e-government services has been increasing over the years and the internet has become the preferred method of contacting the government. Keywords: internet, government, Technology